Rayando el cuerpo : el barrismo, una práctica invisibilizada que se abre espacio en la ciudad (2012)
ABSTRACT: This article is the result of a research work made at Atanasio Girardot and Belén Sport Complexes, in Medellin city, Colombia. The aim of this research is identifying, describing and understanding the surfacing of the barrismo (monkey bars activities) practice in the city, the sense and recognition that it has for its practitioners, while it is a practice that distinguishes, stigmatizes and defines identitary features that make up a masculine way of life. This qualitative research is done as an ethnography that privileges the voice of the barristas, their descriptive and relational profiles by using photo-ethnography and interviews. The results show who they are, what they do and why they do it, their distinctive features, their cultural codes and their position in the city.